Genetic variability, heritability and correlation path analysis in mungbean (Vigna radiata L.wilczek) - Azam, MG; Hossain, MA; Alam, MS; Rahman, KS; Hossain, M (Bangladesh Journal of Agricultural Research, 2018)
The success of crop improvement program largely depends on the nature and magnitude of genetic variability, heritability and characters association. This experiment was undertaken to estimate the extent of genetic variability and relation between yield and related characters. Twenty eight mungbean genotypes were grown at Pulses Research Centre, Ishurdi, Pabna during kharif-I 2015 in a randomized complete block design with three replications to estimate the extent of genetic variability and association between yield and yield related traits. Analysis of variance revealed that all the traits showed highly significant difference among genotypes except seeds per pod. Pods per plant, plant height and 100 seed weight showed high genotypic coefficients of variation (GCV) and phenotypic coefficients of variation (PCV). High broadsense heritability coupled with moderate genetic advance as percent of mean was observed for 100 seed weight, days to flower and pods per plant suggesting preponderance of additive gene action for these characters and selection of such traits might be effective for the improvement of grain yield. Seeds per pod, plant height and pods per plant showed positive significant phenotypic and genotypic correlation with yield. The result of path analysis indicated that pods per plant had maximum direct effect on yield followed by plant height and 100 seed weight and they contribute 31% variation in yield. Bangladesh J. Agril. Res. 43(3): 407-416, September 2018